Michael Cook: Kompromi Polemik Penulisan Al-Qur’an dan Hadis - Nur Hamidah Pulungan (Al-Kauniyah: Jurnal Ilmu Al-Qur'an dan Tafsir, 2024)
This qualitative research using a literature review method examines the profile of an orientalist named Michael Cook as a developer of Western revisionist methods with the creation of his own method which is famously known as The Spread of Isnad. The initial Orientalist mission focused on the spread of missionary liberalism under colonialism with intellectual academic methods such as philology, manuscripts and language studies when studying the Koran and Hadith. The results of Orientalist studies are of course that the majority are skeptical and even weaken Islamic teachings. Most Orientalists claim that Muhammad was an adopter of at least two previous teachings, namely Judaism and Christianity, so there are many similarities in the two products. Polemics of differences between fellow orientalists also cannot be avoided. In reality, not all orientalists agree that the Koran and Hadith are fake products that support Islamic teachings. M. Cook comes with the character of neo-skepticism, namely an attempt to doubt the Prophet's hadith through attempts to develop the theoretical ideas of predecessors such as Schacht.